THE EFFECTIVENESS OF GIVING PINEAPPLE AND CORN PUDDING ON THE REDUCTION OF URIC ACID LEVELS IN THE WORKING AREA PUSKESMAS SOSIAL PALEMBANG CITY - Muzakar; M.N, Fauziah; Susyani; Listrianah (International Journal of Research -GRANTHAALAYAH, 2022)
Background: Gout is a failure of purine metabolism that causes an increase in the concentration of uric acid in the blood. The prevalence of gout in Indonesia in 2018 was 7.3% and in South, Sumatra was 62.4%. One of the non-pharmacological management of gout is by giving pineapple and corn pudding. Purpose: This study was to determine the effect of pineapple and corn pudding on the decrease in blood uric acid levels in hyperuricemia patients. Method: The type of research is a quasi-experiment with a pretest and posttest control group design. This research was conducted from January to February 2021 at the Puskesmas Sosial Palembang City. The research sample was selected by accidental sampling with a total sample of treatment and comparison groups of each of 30 respondents. Result: Data analysis using paired sample t-test and independent sample t-test with the difference in the average value of uric acid levels of the treatment group 0.7 mg / dl (p-value = 0.011) and the comparison group 0.44 mg / dl (p-value = 0.049). While the results of the independent sample t-test are p-value = 0.003. Conclusion: Statistical test results showed that there was an effect of pineapple and corn pudding on the decrease in blood uric acid levels in hyperuricemia patients with differences in the average difference in blood uric acid levels in the treatment group higher than the comparison group.